KINERJA KEUANGAN DAERAH KOTA MAKASSAR PROVINSI SULAWESI SELATAN - Soni, Doni Iyawan (JIM : Journal Of International Management, 2023)
This research is entitled Regional financial performance of Makassar City, South Sulawesi. The problem in this study is How is the level of efficiency of regional expenditure in South Sulawesi Province 2013-2017? 2). What is the level of effectiveness of regional expenditure in South Sulawesi Province 2013-2017? The purpose of this study was to determine the level of efficiency and effectiveness of regional expenditure in South Sulawesi Province in 2013 - 2017. The method is descriptive qualitative approach by looking at Effectiveness Analysis and efficiency of Direct and Indirect Expenditure. The results showed that even the highest percentage in 2017 was only 18.38%. So if you refer to Keynes' theory, it is only natural that the economy does not improve with the increase in regional expenditure every year because regional expenditure is more dominant in indirect expenditure, which is 69%, which basically indirect expenditure is not productive expenditure. Indirect spending is categorized as effective. Meanwhile, direct expenditure is categorized as less effective. Indirect expenditure is categorized as efficient. Meanwhile, direct expenditure is categorized as very efficient.